Central venous access device locking practices in the adult critical care setting: a single-centre, observational study establishing duration of locking per catheter lumen. (27th October 2022) - Ornowska, Marlena; Wittmann, Jessica; Reynolds, Steven
Abstract : Purpose: Central line complications remain a problem in critical care patient populations. Various interventions to prevent or treat complications, such as central line-associated bloodstream infection and occlusion, have been the focus of recent research. Although alternative catheter locking solutions have been shown to be effective in other patient populations, their applicability to the critical care setting remains unclear. Due to the high acuity of critical care patients, it is uncertain whether their central lines remain locked for a duration long enough for alternative locking solutions to provide any effect. Methods: This single-centre, prospective, observational study aimed to gather information about the length of time central line lumens remain in a locked state in the average critical care patient. Baseline rates of various central line complications were also tracked. Results: Results of this study indicate that the majority of central lines will have at least one lumen locked for an average of 36.6% of their time in situ. Conclusions: It is anticipated that this length of time provides enough exposure for alternative locking solutions to potentially make a difference in central line complications in this patient population. Results of this study can be used for planning future multi-centre, randomized controlled trials investigating the efficacy of novel central line locking solutions to prevent central line complications in critically ill patients.